Розробка моделей гібридів кукурудзи груп ФАО 150-600 в умовах зрошення - Вожегова, Р.А.; Лавриненко, Ю.О.; Лашина, М.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. Development and clarification of morphological models of hybrids of corn for the of irrigation south of Ukraine. Methods. Genetic and statistical analysis of selection numbers of hybrids of corn. Results. The article presents data on the development and refinement of morphological models maize hybrids of different maturity groups. The models developed corn hybrids will effectively lead work on a new raw material of corn with desired properties and the appropriate level of implementation of hybrid combinations that enhance the effectiveness of selection process of synthesis of a new generation of hybrid and rapid implementation in agricultural production. Conclusions. For the terms of irrigation of south ofUkraine different models of hybrids of corn of the FAO 150–600 groups are developed.

Key words: maize, hybrid model, yield of grain, plant height, irrigation.